PENGARUH KUALITAS LAYANAN, NILAI PELANGGAN DAN KETERSEDIAAN INFORMASI TERHADAP PENGGUNA JALAN TOL (Studi PT. Jasa Marga Persero Tbk. Cabang Semarang) - Lia Widyayanti, 10.05.51.0125; Prabowo, Rokh Eddy (Students Journal of Economic and Management, 2014)
This study aims to analyze the influence of Service Quality, Customer Value and Availability Information on Toll Road User Satisfaction. The study population was 48,605,257 Traffic seen from the data year 2013, the number of samples is100 Toll Road users. Data obtained directly from the Toll Road users and the techniques use dare primary data with a questionnaires to the respondents Toll Road users. These results indicate that the Service Quality, Customer Value and Availability of information each user satisfaction influence on the Toll Road. When these variables 75 percen to the dependent variable, namely the Toll Road User Satisfaction. This is evident from R2 showed 0,745 based on the calculation of regression.Keywords : Service Quality, CustomerValue and availability information, user satisfaction Tol Road